Derivational Suffixes in Crazy Rich Asians Novel: A Morphological Analysis - Narasuari, Ni Putu Dian; Sri Rahayuni, Ni Ketut (Humanis, 2020)
This study focused on the classification types and identifying the function of derivational suffixes. The data were taken from a novel entitled Crazy Rich Asians by Kevin Kwan. The collected data were analysed by using documentation method and qualitatively analyzed. The analysis was based on the theory of morphological study, particularly suffixes that is proposed by Plag (2002:109). Moreover, Merriam Webster dictionary is used in this study to analyse the word class of suffixes. The findings showed that there are four types of suffixes, such as: nominal suffixes, verbal suffixes, adjectival suffixes, adverbial suffixes. The function of the suffix can be divided into two, which is to class maintaining suffixes and class changing suffixes.